Designing the ultimate general medicine model. Issue 2 (20th February 2022) - Thompson, Campbell H.; Gilbert, Toby R.
Abstract: The ideal model of care in general medicine remains elusive, perhaps because of interhospital heterogeneity in patient population and resource allocation to both general medicine and the medical subspecialties. We explain why successful interventions at one site are not easily applied in another and recommend a nationally coordinated examination of the best general medicine departments' methods of clinical practice improvement.